(untitled) (Revista Sistemas de Producción Agroecológicos, 2024)
Supplementation in fattening sheep in the Piedemonte Llanero region of Colombia is a common practice to meet their nutritional needs due to climatic fluctuations and soil conditions. It is necessary to seek alternatives to preserve forage during summer to maintain its protein value. This study, conducted in Villavicencio, Meta, Colombia, aimed to evaluate the performance of crossbred fattening sheep grazing on Brachiaria spp. with supplementation of corn silage, palm kernel cake, wheat bran, and Tithonia diversifolia (Golden Button). The research was carried out at the University of los Llanos Farm in Villavicencio-Meta, using 12 sheep with an average weight of 19.5 ± 3.6 kg. At the start of the productive management, the sheep were administered Compleland B12 at a dose of 2 ml intramuscularly and dewormed with 1 ml of Febendazole at 25% orally. The sheep were allowed to graze Brachiaria spp. freely and were supplemented with 250 grams of dry matter per day, containing the following treatments: T1: 30% commercial concentrate (CC) + 70% corn silage (CS); T2: 30% CC + 40% CS + 30% palm kernel cake; T3: 30% CC + 40% CS + 30% wheat bran; T4: 30% CC + 40% CS + 30% Golden Button. The sheep were kept in stalls until 10 a.m. for supplementation and then taken out to graze. The analyzed variables included the nutritional content of the four treatments in terms of dry matter (DM), crude protein (CP), fat, crude fiber (CF), and non-nitrogen extract (NNE) in the supplied forages. DM, CP, organic matter (OM), and minerals such as Ca, Mg, P, and Cu were determined through foliar analysis. The sheep were evaluated for DM, CP, fat, CF, NNE consumption, in vivo digestibility of the DM of the supplied treatments, and weight gain. The statistical design was completely randomized, using Duncan’s comparative test. For blood parameters, the Student’s T-test was used to measure before and after supplementation. The contents of DM, CP, OM, Ca, Mg, P, and Cu in the forages indicated that Golden Button (Tithonia diversifolia) has a good protein content of 17.39%, with higher (P<0.05) mineral values such as Ca (1.33%), Mg (0.25%), and P (0.13%) compared to Brachiaria spp. and corn silage, making it an economical source of these nutrients and thus a suitable supplement for ruminants whose base diet consists of these forages. The highest daily DM consumption (P<0.05) was recorded for T1 (908.12 g) and T4 (906.18 g), with T4 also showing superior daily protein consumption (1232.42 g). Although T1 had the highest DM digestibility (P<0.05) at 81.05% compared to T2, T4, and T3 (71.14%, 70.61%, and 66.71%, respectively), the daily weight gains for T1 and T2 were the highest (P<0.05) and similar between them: 188.97 g and 196.3 g versus T3 and T4: 154.3 g and 140.1 g, respectively. This suggests that a good supplement with sufficient protein can replace commercial concentrate. Total protein in blood serum increased after supplementation (P<0.05) in T1 (5.27 to 6.58 g/dl), T3 (5.69 to 6.96 g/dl), and T4 (6.44 to 7.77 g/dl). Most values found in each treatment did not differ within the range of 6-7.9 g/dl. Cholesterol concentrations also rose after supplementation. There was a positive change in ruminal transit and absorption, as well as increased daily weight gain. Glucose concentrations remained constant in T4 and decreased (P<0.05) in the other treatments after supplementation, while albumin remained stable in T1 and T2 but decreased in T3 and T4. Clearly, supplementation affects the physiological and productive mechanisms of the animal, as observed in the results of DM digestibility, weight gain, and blood chemistry. Most values were within the established normal parameters for sheep.